Green bonds as a tool against climate change? - Serena Fatica; Roberto Calogero Panzica (Publications Office of the European Union, 2020)
While green bonds are becoming increasingly popular in the corporate finance practice, little is known about their implications and effectiveness in terms of issuers' environmental engagement. Using matched bond-issuer data, we test whether green bond issues are associated to a reduction in total and direct (scope 1) emissions of non-financial companies. We find that, compared to conventional bond issuers with similar financial characteristics and environmental ratings, green issuers display a decrease in the carbon intensity of their assets after borrowing on the green segment. The decrease in emissions is more pronounced, significant and long-lasting when we exclude green bonds with refinancing purposes, which is consistent with an increase in the volume of climate friendly activities due to new projects. We also find a larger reduction in emissions in case of green bonds that have external review, as well as those issued after the Paris Agreement.
Keywords: G12; Q50; Q51; 330; climate change; green bonds; impact investing; corporate sustainability; environment